2021
DOI: 10.1371/journal.pone.0258087
|View full text |Cite
|
Sign up to set email alerts
|

On the effect of international human migration on nations’ abilities to attain CO2 emission-reduction targets

Abstract: I merge publicly available data on CO2 emissions, with patterns of human movement, to analyze the anticipated effects of human migration on the abilities of nations to attain 2030 UNFCCC CO2 emission targets. I do so at both global (175 countries) and national (Canada and the USA) scales. The analyses reveal that mean per capita CO2 emissions are nearly three times higher in countries with net immigration than in countries with net emigration. Those differences project a cumulative migration-induced annual inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…These figures imply that many cities around the world are facing a mass influx of migrants. With increased migrant settlements, the demand for locally provided goods and services is increased, accessing to common resources becomes more limited (Squalli, 2010), public services are overburdened, energy consumption and greenhouse gas emissions are increased (Morris, 2021). Moreover, municipality level standards, such as the quality of waste management and environmental protection services, will be under pressure (Squalli, 2009).…”
Section: Ijccsmmentioning
confidence: 99%
See 3 more Smart Citations
“…These figures imply that many cities around the world are facing a mass influx of migrants. With increased migrant settlements, the demand for locally provided goods and services is increased, accessing to common resources becomes more limited (Squalli, 2010), public services are overburdened, energy consumption and greenhouse gas emissions are increased (Morris, 2021). Moreover, municipality level standards, such as the quality of waste management and environmental protection services, will be under pressure (Squalli, 2009).…”
Section: Ijccsmmentioning
confidence: 99%
“…Studies revealed that per capita CO 2 emissions are nearly three times higher in countries with net immigration than in countries with net emigration (Morris, 2021), and the higher migrant settlements are associated with worse environmental outcomes, such as per capita waste, per capita distributed freshwater and wastewater (Aksoy and Tumen, 2021). The mass influx of population into cities will accelerate the process of urbanization, leading to urban greening reduction.…”
Section: Analytical Framework: Formation Of Index Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the data provided in [18][19][20][21]. During the last five years, the average annual carbon dioxide emissions have been 30-38 billion metric tons [22][23][24]. As we can see, the current annual figure of anthropogenic carbonization is comparable with the natural flows of this gas between the troposphere and stratosphere.…”
Section: Carbonization Of the Earthmentioning
confidence: 99%